The Impact of Immigrants on the Number and Type of Births - Neset Gumusburun; Ergun Mendes (Makara Journal of Health Research)
Background: Although cesarean section is a life-saving procedure in certain situations, it may result in complications for maternal and infant health when conducted, especially for nonmedical purposes. The civil war in Syria has significantly modified the demographic and ethnic structure of Turkey, which has affected the number and type of births occurring here. In this study, we aimed to determine the effect of the increasing Syrian refugee patient population on primary cesarean section rates in Kilis/Turkey.